A new national data collection for congenital anomalies in England and Wales. (18th April 2012) - Springett, A; Draper, ES; Rankin, J; Rounding, C; Thompson, R; Tucker, D; Wellesley, D; Morris, JK
Abstract : Aim: In 2009 the National Congenital Anomaly System (NCAS) run by the Office for National Statistics (ONS) ceased data collection. In 2011, the Department of Health funded the British Isles Network of Congenital Anomaly Registers (BINOCAR) to provide surveillance of congenital anomalies in England and Wales.1 This study highlights the strengths and weaknesses of the new BINOCAR surveillance system. Methods: Five anomalies (anencephalus, spina bifida, encephalocele, hydrocephalus and Down syndrome), with consistent coding between 1995 and 2008, were identified from NCAS and BINOCAR. Prevalence and trends over time were compared between the two systems. Results: In 1995-2008, the prevalence in BINOCAR data compared with NCAS data for the five anomalies ranged from 1.9 times [95% CI: 1.7-2.0] higher for anencephalus to 3.1 times [95% CI: 2.9-3.4] higher for hydrocephalus. Trends for both NCAS and BINOCAR data showed a statistically significant decrease in the prevalence of spina bifida (<0.001 and 0.02 respectively) and increase in Down syndrome (<0.001 and 0.003 respectively) with no change in the prevalence of encephalocele. However, whilst NCAS showed a significant decrease in the prevalence of both anencephalus (p=0.01) and hydrocephalus (p=0.01) BINOCAR showed no significant trend (p=0.06 and p=0.91 respectively). Conclusion: BINOCAR had significantly higher ascertainment than NCAS and this is likely to explain the differences in trends. However, the current registers only cover 35% of England and Wales and this limits the power in analysing trends. For adequate surveillance national coverage by congenital anomaly registers is required.